2017
DOI: 10.1146/annurev-neuro-072116-031407
|View full text |Cite
|
Sign up to set email alerts
|

Learning in the Rodent Motor Cortex

Abstract: The motor cortex is far from a stable conduit for motor commands and instead undergoes significant changes during learning. An understanding of motor cortex plasticity has been advanced greatly using rodents as experimental animals. Two major focuses of this research have been on the connectivity and activity of the motor cortex. The motor cortex exhibits structural changes in response to learning, and substantial evidence has implicated the local formation and maintenance of new synapses as crucial substrates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
81
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(101 citation statements)
references
References 147 publications
6
81
0
Order By: Relevance
“…Once animals learn the stereotyped motor sequences required for our task, they are expressed in largely unaltered form over long periods of time 35 , suggesting the formation of stable memories. While prior studies have suggested that motor memories are stored in motor cortex [85][86][87][88][89][90][91][92][93][94][95] and/or at synapses between motor cortex and striatum 23,27,31,32,34 , neither of these neural substrates are required for executing the behaviors we train 11,35 . The crucial involvement of the DLS in both motor sequence learning ( Fig.…”
Section: Reversal Of Long-term Synaptic Plasticity In Dls Disrupts Pementioning
confidence: 88%
“…Once animals learn the stereotyped motor sequences required for our task, they are expressed in largely unaltered form over long periods of time 35 , suggesting the formation of stable memories. While prior studies have suggested that motor memories are stored in motor cortex [85][86][87][88][89][90][91][92][93][94][95] and/or at synapses between motor cortex and striatum 23,27,31,32,34 , neither of these neural substrates are required for executing the behaviors we train 11,35 . The crucial involvement of the DLS in both motor sequence learning ( Fig.…”
Section: Reversal Of Long-term Synaptic Plasticity In Dls Disrupts Pementioning
confidence: 88%
“…There is a strong body of evidence to suggest that a reduction in cortical inhibitory tone is critical for the induction of M1 plasticity (Bachtiar & Stagg, ; Peters et al . ). Specifically, a reduction in GABAergic signalling appears crucial to the induction of long‐term potentiation (LTP)‐like plasticity in M1 (Castro‐Alamancos et al .…”
Section: Introductionmentioning
confidence: 97%
“…Circuits within supragranular layers appear crucial for processing task‐relevant sensory information (Thura & Cisek, , ) and for learning (Peters et al . , ; Chen et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…In the primary motor cortex (M1), circuits located in different layers appear to play different roles, reflecting their distinct anatomical connections. Circuits within supragranular layers appear crucial for processing task-relevant sensory information (Thura & Cisek, 2014, 2016 and for learning (Peters et al 2014(Peters et al , 2017bChen et al 2015). By contrast, activity in infragranular layer 5 is correlated with the prevention and production of movement (Ebbesen & Brecht, 2017;Peters et al 2017a;Soteropoulos, 2018).…”
Section: Introductionmentioning
confidence: 99%